Existential presupposition projection from none? An experimental investigation - Zehr, Jérémy; Bill, Cory; Tieu, Lyn; Romoli, Jacopo; Schwarz, Florian (Proceedings of the Amsterdam Colloquium, 2015)
The question of how presuppositions project from the scope of quantificational sentences, and in particular negative quantificational sentences such as none in (1), continues to be controversial, both theoretically and empirically: some theories only predict the existential presupposition projection reading in (1-a) (for example, [2, 3, 26, 13]), while others derive the universal projection reading in (1-b) ([15, 20, 21, 12, 10, 11], among others). In addition, any theory has to account for presupposition suspension, yielding an interpretation without a (global) presupposition (1-c). (1) None of the bears won the race. a. At least one of the bears participated and none of them won. b. All of the bears participated and none of them won. c. None of the bears both participated and won. Previous empirical studies have found evidence for universal projection ([7]), while others have provided evidence for alternatives to universal projection ([24, 14]). To our knowledge, however, there exists no definitive positive evidence for the existential reading in (1-a). We report a study that directly compares the existential, universal, and presuppositionless readings of (1) through the use of a ‘covered box’ picture selection task [16, 5]. We find clear evidence for existential readings (as well as presuppositionless readings), but no evidence for universal ones. This result challenges theories that predict only universal readings. Our results, taken together with those reported in [7], suggest that any adequate account of presupposition projection must be able to explain all three interpretive options in (1).